Factors Affecting The Risk Of Postpartum Depression - Sulistiani Sulistiani; Sri Handayani; Cesa Septiana Pratiwi (Jurnal Health Sains, 2022)
Postpartum depression is a common problem that occurs in the perinatal period around 7-13% of postpartum women can cause short-term and long-term effects that will have an impact on the mother, baby, and social environment. This study aimed to examine the evidence related to the factors that influence the risk of postpartum depression. Scoping review using the framework of Arksey and O'Malley, who conducted a focused review with the PEO framework, conducted a literature search using relevant databases and gray literature, selected relevant studies using inclusion and exclusion criteria, and conducted a critical assessment for assessment. article quality, perform data extraction, analyze and report results. 10 articles were selected and received Grade A. 10 articles were obtained from research conducted in developing countries, namely 2 articles from Nepal, 1 from Malaysia, 1 from Uganda, 2 articles from Indonesia, 1 from Egypt, 1 from Kosovo, 1 Iran, and 1 an article from Ethiopia 14 factors that influence the risk of postpartum depression, namely age, parity, gender, unplanned/expected pregnancy, family mental health history, social support, history of anxiety/depression, family problems, obstetric complications, parenting stress, type of delivery, financial problems, spouse violence. Screening and intervention programs for women prone to postpartum depression should be carried out during pregnancy and are recommended to address perinatal mental health problems and improve maternal mental health.